Longitudinal Profile of the Objects Included in the Gravel Roads Paving Programme of Lithuania - Vilimas Gintalas (The Baltic Journal of Road and Bridge Engineering, 2007)
For the implementation of the Gravel Roads Paving Programme on the Lithuanian roads the reconstruction projects of the existing gravel roads are being prepared. This article studies the problems caused by taking the design solutions and correcting a longitudinal road profile of the objects included in the Gravel Roads Paving Programme. It also gives the results of investigating a longitudinal profile of gravel roads under the supervision of the State Enterprise Telsiai Regional Roads Administration. Based on investigation results, the design radii of vertical curves are suggested and recommended to use in projects for paving gravel roads.